Media, identity, and online communities in a changing Arab world. (May 2019) - Mohamed, Eid; Douai, Aziz; Iskandar, Adel
Our Special Issue captures the interplay of media, politics, religion, and culture in shaping Arabs' search for more stable governing models at crossroads of global, regional, and national challenges through systematic and integrated analyses of evolving and contested Arab visual and performing arts, including media (traditional and alternative), in revolutionary and unstable public spheres. This special issue examines the role of new media in the construction of online communities in the Arab world. It contributes to the understanding of how user-generated content empowers these new publics and the novel communities established by user comments on social media and news websites. Specifically, it explores these online communities and their perceptions of the role of user-generated content to contribute to politics, and potentially engage other citizens in the public debate.